Periodic solutions to reversible second order autonomous systems with commensurate delays - Balanov, Zalman; Chen, Fulai; Guo, Jing; Krawcewicz, Wiesław (Topological Methods in Nonlinear Analysis, 2021)
Existence and spatio-temporal patterns of periodic solutions to second order reversible equivariant autonomous systems with commensurate delays are studied using the Brouwer O(2) × Γ × Z_2-equivariant degree theory, where O(2) is related to the reversing symmetry, Γ reflects the symmetric character of the coupling in the corresponding network and Z_2 is related to the oddness of the right-hand side. Abstract results are supported by a concrete example with Γ = D_6 - the dihedral group of order 12.